2010
DOI: 10.1021/jp105155a
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Excitation of “Exciplex Tuning” for Luminescent Nanoclusters of Dicyanoargentate(I) Ions Doped in Different Alkali Halide Crystals

Abstract: Luminescent nanoclusters of linear dicyanoargentate(I) ions doped in different alkali halide single crystals (NaF, NaCl, NaBr, and KCl) have been investigated. Site-selective excitation of the different nanoclusters results in the appearance of emission bands which are assigned to different luminescent {[Ag(CN)2]−} n nanoclusters in the host lattices. The nanoclusters of [Ag(CN)2]− in the alkali halides display energy tunability over a wide wavelength interval. The ab initio DFT calculations show that for nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
2
10
1
Order By: Relevance
“…19−22 Detectable emissions with Au−Au bond formation have been observed even in intermolecular systems in solutions; i.e., [Au(CN) 2 − ], one of the simplest Au(I) complexes, exhibits emission after excited-state Au−Au bond formation in oligomers. 3,23,24 Patterson and co-workers performed pioneer studies of the excited-state oligomers of Au(I) complexes, including detailed studies of the emissions in solutions 3,[9][10][11]17,25,26 and solid states 10,25,27 as well as their applications. 9,10,17,23,28 In particular, light-emitting molecular assemblies with flexible structures and large oligomers such as oligomers larger than tetramers were observed in [Au(CN) 2 − ] n aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19−22 Detectable emissions with Au−Au bond formation have been observed even in intermolecular systems in solutions; i.e., [Au(CN) 2 − ], one of the simplest Au(I) complexes, exhibits emission after excited-state Au−Au bond formation in oligomers. 3,23,24 Patterson and co-workers performed pioneer studies of the excited-state oligomers of Au(I) complexes, including detailed studies of the emissions in solutions 3,[9][10][11]17,25,26 and solid states 10,25,27 as well as their applications. 9,10,17,23,28 In particular, light-emitting molecular assemblies with flexible structures and large oligomers such as oligomers larger than tetramers were observed in [Au(CN) 2 − ] n aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…3,23,24 Patterson and co-workers performed pioneer studies of the excited-state oligomers of Au(I) complexes, including detailed studies of the emissions in solutions 3,[9][10][11]17,25,26 and solid states 10,25,27 as well as their applications. 9,10,17,23,28 In particular, light-emitting molecular assemblies with flexible structures and large oligomers such as oligomers larger than tetramers were observed in [Au(CN) 2 − ] n aqueous solutions. Such flexibility and large size are unique points of the oligomers in fluid media because their formations require large displacements of gold atoms and such a large change will be difficult to achieve in solid states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure results show that the Ag–Ag bond distance is 3.11 Å and the low energy Ag–Ag vibrational frequency of about 75–125 cm −1 given by Raman indicates the presence of direct argentophilic interaction in Tl[Ag(CN) 2 ]. Since then, our group has reported a series of d 10 metal cyano compounds in nano systems [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. We found that due to the formation of different size exciplexes, these nano systems show interesting photophysical and photochemical behaviors, such as emission tunability, thermochromism, and optical memory.…”
Section: Introductionmentioning
confidence: 99%
“…The conflicting photophysical behavior between the Au and Ag complexes made assignment of the emission bands difficult based solely on previously reported [Au(CN) 2 ] – /[Ag(CN) 2 ] – systems , , . As mentioned, emission in these systems can arise from a localized MLCT, a MMLCT, or MC transition.…”
Section: Resultsmentioning
confidence: 99%